PENERAPAN TEKNOLOGI TEPAT GUNA BIO FAD’S DALAM UPAYA MENINGKATKAN PENDAPATAN NELAYAN SKALA KECIL PADA MUSIM PACEKLIK - Irman Halid; Nasruddin Djunaedi (Jurnal Abdi Insani, 2022)
The fishermen group on the coast of Karang-karangan Village, Luwu Regency, South Sulawesi is a small fishing community. Fishing activity is classified as simple and inherited from the ancestors. Fish "malaja" as a mainstay fishery commodity in Luwu Regency is currently in the over-exploited category which will cause the extinction of this resource. An alternative is needed during the famine season through the introduction and application of Bio-FAD's technology as an alternative business of catching fish when sero fishing gear decreases. The aim of the activity is to increase the knowledge, skills and income of fishermen, especially during the famine season through the provision of business and institutional management materials and practices as well as practical training on making Bio FAD's technology. Activity methods in the form of: Focus Group Discussion (FGD), business and institutional management training and training on making Bio-FAD's are intended to transfer appropriate technology as an alternative solution to fishing efforts during the famine season and evaluate activities after the entire program has been implemented. Strengthening business group institutional management materials, simple bookkeeping with the aim of recording, reporting and analysis of business conditions as well as training on making Bio FAD's into new knowledge that can be implemented by group managers. There was an increase in the understanding of the participants, namely the average before the training was 46 and after the training it was 72 with an average increase of 36.11%.